Cardiorenal and hepatorenal syndrome - Anand Bhutada; Abhijit Choudhary; Atul Kapse; Vinayak Patki (Wolters Kluwer Medknow Publications, 2018)
Cardiorenal syndrome(CRS) is an interdependent involvement of the heart and the kidney that leads to high morbidity, recurrent readmissions and grave prognosis. Early use of slow high-dose intravenous diuretics, dialysis with ultrafiltration for treatment of congestion, inotropes and left ventricular assistant device to stabilize the hemodynamics and maintenance of the renal perfusion are the vital component for a short period of time. Hepatorenal syndrome (HRS) is a unique form of functional renal failure associated with progressive liver failure. It carries worst prognosis among all causes of renal failure in children with liver disease. Liver transplantation is the definitive treatment of HRS. Vasoconstrictor therapy with albumin and Renal replacement therapy are used as a bridge to liver transplant for patients who are unresponsive to medical therapy.